Molecular characterization of begomovirus–betasatellite–alphasatellite complex associated with okra enation leaf curl disease in Northern Sri Lanka - Emmanuel, Christy Jeyaseelan (3 Biotech, 2020)
Okra enation leaf curl is a newly emerging disease in commercial okra cultivation fields in Northern Sri Lanka. The present study aimed to identify and characterize the causative begomovirus and associated satellites. Okra plants showing the enation leaf curl disease symptoms were collected from Vavuniya and Jaffna districts of Northern Province. The PCR diagnostic and genome sequencing revealed that the symptomatic okra plants are associated with begomovirus, betasatellite, and alphasatellite complex. The begomovirus isolates shared 98.2–99.7% nucleotide identity with Okra enation leaf curl virus. The betasatellites showed 96–98.8% nucleotide identity with Bhendi yellow vein mosaic betasatellite which is usually associated with Bhendi yellow vein mosaic disease. Two distinct alphasatellite species, Okra leaf curl alphasatellite and Bhendi yellow vein mosaic alphasatellite, were identified in leaf samples with enation leaf curl disease. The disease was transmitted by whiteflies from diseased plants to healthy plants. Hybrid varieties were more susceptible to the disease compared to cultivated varieties. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13205-020-02502-z) contains supplementary material, which is available to authorized users.